Pengembangan Media Pembelajaran Praktikum Akuntansi Perusahaan Dagang Berbasis Simulation Accounting (SIMACC) pada Peserta Didik Kelas XI SMK Negeri di Surabaya - Eka Izzatil Hikmah; Susanti (Mataram University, 2026)
The digital-era transformation of education encourages the use of technology to enhance student competence. However, practical accounting instruction for trading companies in several state vocational high schools (SMK) in Surabaya still faces challenges. These include suboptimal use of instructional media, manual processing of accounting cycles, and students' limited understanding of transaction analysis and financial statement preparation. Consequently, this study aims to develop an instructional tool—specifically, a trading company accounting practice application named Simulation Accounting (SIMACC). The study employs the ADDIE development model, comprising the stages of Analysis, Design, Development, Implementation, and Evaluation. Trial subjects included 15 students for the small-group trial and 29 students for the large-scale trial, drawn from Grade XI accounting classes at state vocational high schools in Surabaya. Data collection instruments consisted of expert validation questionnaires and student response surveys. The results showed expert validation scores of 93% for content and 94.5% for media, along with an 88% positive response from students; these figures indicate that the developed media falls into the